Interoperability between Information Systems of Portuguese Higher Education Institutions - Lígia M. Ribeiro (2016)
The main thrust of this work is to present an interoperability platform between information systems of higher education institutions in Portugal and the main advantages and benefits its use has already allowed within an academic community of about 100,000 users. This interoperability platform, running on a cloud computing environment, was a major result of a project called "IES+Perto", meaning "Higher Education Institutions Closer", involving some of the most prestigious Portuguese universities and the largest polytechnic in the country. It was developed with a unifying but not intrusive perspective, so that each institution would continue to be solely responsible for the organization and delivery of its information. A common mobility strategy for digital content supported by an application for mobile devices, and a set of services for electronic data transfer between institutions for the academic processes of student national mobility and joint courses of study, have been developed using the interoperability platform. The project IES+Perto and the interoperability platform in particular have contributed very positively to innovation, administrative modernization and electronic management of the institutions involved, creating conditions for the extension of services to other higher education institutions, as has already happened by supporting new initiatives that the project IES+Perto proponents and other higher education institutions submitted for funding under a new application to the National Administrative Modernization Support System, which were approved.